2020
DOI: 10.28991/cej-2020-03091524
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Compressive Strength Analysis for Cement Mortar with Industrial Waste Materials

Abstract: Cement production uses large quantities of natural resources and contributes to the release of CO2. In order to treat the environmental effects related to cement manufacturing, there is a need to improve alternative binders to make concrete. Accordingly, extensive study is ongoing into the utilization of cement replacements, using many waste materials and industrial. This paper introduces the results of experimental investigations upon the mortar study with the partial cement replacement. Fly ash, silica fume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Due to photosynthesis and biochemical interactions, silica and a barrier layer are formed on the rice plant's stem and husk surfaces [81]. These layers have developed to shield the rice plant and its grains from environmental changes such as temperature variations, excessive water evaporation, and microbial assault [81].…”
Section: Composition Of Rice Huskmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to photosynthesis and biochemical interactions, silica and a barrier layer are formed on the rice plant's stem and husk surfaces [81]. These layers have developed to shield the rice plant and its grains from environmental changes such as temperature variations, excessive water evaporation, and microbial assault [81].…”
Section: Composition Of Rice Huskmentioning
confidence: 99%
“…Due to photosynthesis and biochemical interactions, silica and a barrier layer are formed on the rice plant's stem and husk surfaces [81]. These layers have developed to shield the rice plant and its grains from environmental changes such as temperature variations, excessive water evaporation, and microbial assault [81]. Approximately 20-30% of the rice husk is made up of mineral components, including silica and metallic residues containing magnesium (Mg), iron (Fe), and sodium (Na).…”
Section: Composition Of Rice Huskmentioning
confidence: 99%
“…The outcomes elucidated that the whole replacements presented the strength development. Such enhancement was less in the premature ages and increased at the advanced ages compared to the control specimens [8]. Joshaghani (2017) study the effect of nano-silica and sugar cane bagasse ash on the mechanical and durability properties of mortar and found that nano-silica improved mechanical and durability properties of mortar.…”
Section: Introductionmentioning
confidence: 99%
“…Strength properties are decreased with the increase of fly ash volume in the cement and not compensated till 90 days. After one year, the resistance of the concrete containing Fly ash generally exceeds that of the control group (100% Portland cement) due to the influence of pozzolanic materials, which favorize the formation of new calcium silicate hydrate (CSH) instead of Calcium Hydroxide (CH) [5,6].…”
mentioning
confidence: 99%